Application of Bat Algorithm for The Detection of Hidden Nodes in IEEE802.11ah Networks - Fapohunda, Kofoworola; Paulson, Eberechukwu Numan; Suleiman, Zubair; Saliu, Oladimeji; Michael, David; Mohammed Yusof, Kamaludin (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Hidden node problem sometimes referred to as frequent packets collision that mostly leads to loss of packets is no longer new in wireless networks because it affects the previous IEEE802.11 standards. The new IEEE802.11ah standard which is also a sub-standard of IEEE 802.11 is no exemption. As a matter of fact, IEEE802.11ah suffers from a hidden node problem more than networks (IEEE 802.11a/b/n/ac) due to their wider coverage which is up to 1km, high number of devices they can support (over 8000 nodes to one AP) and frequent simultaneous sleeping and sending of the nodes (power saving mode). A few researchers have worked on this hidden node problem in IEEE802.11ah but could not get a lasting solution to it. Therefore, this paper proposes an algorithm which detects hidden nodes and also proposes a theoretical solution based on previous works which was also experimentally verified through the BIHD-CM.